2014
DOI: 10.1158/1078-0432.ccr-13-3045
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Presurgical Trial of Transdermal 4-Hydroxytamoxifen Gel versus Oral Tamoxifen in Women with Ductal Carcinoma In Situ of the Breast

Abstract: Purpose Local transdermal therapy to the breast may achieve effective target-organ drug delivery, while diminishing systemic effects. We conducted a randomized, double-blind, placebo-controlled phase II trial comparing transdermal 4-hydroxytamoxifen gel (4-OHT) to oral tamoxifen (oral-T) in women with ductal carcinoma in-situ (DCIS). Methods 27pre and postmenopausal women were randomized to 4-OHT (4mg/day) or oral-T (20mg/day) for 6-10 weeks before surgery. Plasma, nipple aspirate fluid, and breast adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 46 publications
3
67
0
1
Order By: Relevance
“…It is found clinically that tamoxifen can significantly improve overall and relapse-free survival rates of all stages of patients with ER-positive breast cancer. 2 Studies showed tamoxifen can reduce the incidence of contralateral breast cancer. 3 Therefore, the drug has been approved as a prophylactic agent to prevent breast tumor.…”
mentioning
confidence: 99%
“…It is found clinically that tamoxifen can significantly improve overall and relapse-free survival rates of all stages of patients with ER-positive breast cancer. 2 Studies showed tamoxifen can reduce the incidence of contralateral breast cancer. 3 Therefore, the drug has been approved as a prophylactic agent to prevent breast tumor.…”
mentioning
confidence: 99%
“…45 Tamoxifen metabolites 4-hydroxytamoxifen and N-desmethyl-4hydroxytamoxifen, which possess a much stronger ER inhibitory activity, 46 could be secreted in bile and participate in enterohepatic circulation. 45 Tamoxifen metabolites 4-hydroxytamoxifen and N-desmethyl-4hydroxytamoxifen, which possess a much stronger ER inhibitory activity, 46 could be secreted in bile and participate in enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…For breast cancer, approaches have included implantable hydrogels, wafers, rods, and films that act as depots (12), which are often designed to biodegrade and thus eliminate the need for surgical removal, topical applications that facilitate transdermal delivery (19, 20), intraductal administration (21, 22), and iontophoretic devices that utilize electric fields to drive and direct drug diffusion (23, 24). An adipose depot has several advantages over these other approaches.…”
Section: Discussionmentioning
confidence: 99%